Arberesh Contribution in the National Movement for the Unity of Italy - Tare, Denisa (Mediterranean Journal of Social Sciences, 2012)
The favorable geographical position between Italy and Albania has led to the maintaining of friendly relations between thesetwo neighboring countries, in spite of their inheriting different traditions and cultures. At the time of Garibaldi, Italy's remarkable figureconsidered as its national hero, the links between the two peoples separated by the same sea grew further. This strengthening ofbilateral ties came as a result of the deepening of Albanian emplaecements on several Italian regions. In Italy, the Arbereshes gave animportant contribution to the unity of their second homeland in 1860-1871. In this study will be demonstrated their contribution in theeffort for the unification of Italy and will be treated the mutual respect between the two neighboring countries, a respect expressed notonly through mere words, but through the concrete assistance Garibaldi wanted to provide through a Balkan expedition in favor offreedom and independence of peoples, among which was to be included also Albania. Bilateral ties were further strengthened as a resultof Garibaldi’s approach. In letters sent to De Rada, Dora d’Idistria linked the triumph of Garibaldi’s movement to the Albanian liberationmovement. Also Garibaldi himself, in his proclamations, declared to owe much to the "brave generous Albanians". Relying on thisproclamation, he clearly expresed his respect and appreciation for the Albanians. Garobaldi’s opinion on the bravery of Albanians isreinforced in the letters written by him to D’Istria. She would state: "Garibaldi is the best judge on the issue of heroism". He had seen theAlbanians in the Italian colonies on the battle fileds and wrote: "The issue of Albanians is mine; I would certainly be happy to usewhatever is left of my life in favor of that brave people. The support of many courageous patriots helped Garibaldi, as he passed to thesouth of Italy, welcomed by the Arberesh fighters in the area with an unprecedented enthusiasm...